Analysis of healthy lifestyle (diet, physical activity, and healthy behavior) in the employees of Dar Al Uloom University - Mohammed, Redhwan Ali Esmail (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The study aimed to assess the reality of healthy lifestyle among the employees of Dar Al Uloom University, to determine the level of obesity among the employees and also to determine the differences in the reality of healthy lifestyle among the students of Dar Al Uloom University according to the study variables (adjective, gender, and age). The researcher used the descriptive analytical approach that fits with the nature of this study. The study sample amounted to 184 of individuals (125 male and female students), (42 faculty members), (17 employees). The researcher used a measure of a healthy lifestyle includes three axes (healthy food, physical activity, and healthy behavior), in addition to defining a body mass indicator to determine degrees of obesity. The results showed that the employees of Dar Al Uloom University are practicing a moderately healthy lifestyle, and that the percentage of obesity was 22.58%, regarding overweight was 37.10%, and healthy weight with a percentage of 40.32%. The results also showed that faculty and staff members have more commitment to a healthy lifestyle by students in the axes of food and healthy behavior, and that males and females, and different other age groups share the same view points and prospective about the reality of a healthy lifestyle. The study recommended spreading awareness of the importance of practicing physical activities for university employees as a way of life, and the necessity of interest in spreading nutritional and health awareness among the university employees by holding different sports and awareness events.